The evolutionarily conserved TSC/Rheb pathway activates Notch in tuberous sclerosis complex and Drosophila external sensory organ development - Magdalena Karbowniczek; Diana Zitserman; Damir Khabibullin; Tiffiney Hartman; Jane Yu; Tasha Morrison; Emmanuelle Nicolas; Rachel Squillace; Fabrice Roegiers; Elizabeth Petri Henske (The Journal of Clinical Investigation, 2010)
Mutations in either of the genes encoding the tuberous sclerosis complex (TSC), TSC1 and TSC2, result in a multisystem tumor disorder characterized by lesions with unusual lineage expression patterns. How these unusual cell-fate determination patterns are generated is unclear. We therefore investigated the role of the TSC in the Drosophila external sensory organ (ESO), a classic model of asymmetric cell division. In normal development, the sensory organ precursor cell divides asymmetrically through differential regulation of Notch signaling to produce a pIIa and a pIIb cell. We report here that inactivation of Tsc1 and overexpression of the Ras homolog Rheb each resulted in duplication of the bristle and socket cells, progeny of the pIIa cell, and loss of the neuronal cell, a product of pIIb cell division. Live imaging of ESO development revealed this cell-fate switch occurred at the pIIa-pIIb 2-cell stage. In human angiomyolipomas, benign renal neoplasms often found in tuberous sclerosis patients, we found evidence of Notch receptor cleavage and Notch target gene activation. Further, an angiomyolipoma-derived cell line carrying biallelic TSC2 mutations exhibited TSC2- and Rheb-dependent Notch activation. Finally, inhibition of Notch signaling using a γ-secretase inhibitor suppressed proliferation of Tsc2-null rat cells in a xenograft model. Together, these data indicate that the TSC and Rheb regulate Notch-dependent cell-fate decision in Drosophila and Notch activity in mammalian cells and that Notch dysregulation may underlie some of the distinctive clinical and pathologic features of TSC.